2014
DOI: 10.1103/physrevb.89.104513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic field on the photon detection in thin superconducting meander structures

Abstract: We have studied the influence of an externally applied magnetic field on the photon and dark count rates of meander-type niobium nitride superconducting nanowire single-photon detectors. Measurements have been performed at a temperature of 4.2 K, and magnetic fields up to 250 mT have been applied perpendicularly to the meander plane. While photon count rates are field independent at weak applied fields, they show a strong dependence at fields starting from approximately ±25 mT. This behavior, as well as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 32 publications
7
31
0
Order By: Relevance
“…This functional dependence of the dark-count rate R DC has been confirmed in TaN and NbN SNSPD up to ∼ 100 mT [61,67], as shown in figure 4(b). Furthermore, these studies have found evidence that the dark counts originate in the turnarounds of the meander structure.…”
Section: Dark Countssupporting
confidence: 66%
“…This functional dependence of the dark-count rate R DC has been confirmed in TaN and NbN SNSPD up to ∼ 100 mT [61,67], as shown in figure 4(b). Furthermore, these studies have found evidence that the dark counts originate in the turnarounds of the meander structure.…”
Section: Dark Countssupporting
confidence: 66%
“…This theory predicts an exponential increase of count rate as a function of applied field, at constant bias current. As in the previous experiments, 13,15 we find that the rate of exponential increase predicted by this theory is an order of magnitude away from the experimental value.…”
supporting
confidence: 68%
“…13,39,40 We conclude that there is a difference in the nature of photon and dark counts in SSPDs: photon counts scale with a field scale B C inherent to the material, whereas dark counts scale with the change in critical current under the influence of magnetic field, which depends on geometry. This difference between photon and dark counts is as of yet unexplained and carries implications for the design of SSPDs: it means that the only way in which an SSPD can be made more efficient by an applied magnetic field is by choosing a geometry where the critical current is not adversely affected by the applied field such as a spiral.…”
Section: -mentioning
confidence: 82%
See 2 more Smart Citations